Microcirculatory blood flow during cardiac arrest and cardiopulmonary resuscitation does not correlate with global hemodynamics: an experimental study - Krupičková, Petra; Mlček, Mikuláš; Huptych, Michal; Mormanová, Zuzana; Bouček, Tomáš; Belza, Tomáš; Lacko, Stanislav; Černý, Miloš; Neužil, Petr; Kittnar, Otomar; Linhart, Aleš; Bělohlávek, Jan (Journal of translational medicine, 2016)
BACKGROUND: Current research highlights the role of microcirculatory disorders in post-cardiac arrest patients. Affected microcirculation shows not only dissociation from systemic hemodynamics but also strong connection to outcome of these patients. However, only few studies evaluated microcirculation directly during cardiac arrest (CA) and cardiopulmonary resuscitation (CPR). The aim of our experimental study in a porcine model was to describe sublingual microcirculatory changes during CA and CPR using recent videomicroscopic technology and provide a comparison to parameters of global hemodynamics. METHODS: Cardiac arrest was induced in 18 female pigs (50 ± 3 kg). After 3 min without treatment, 5 min of mechanical CPR followed. Continuous hemodynamic monitoring including systemic blood pressure and carotid blood flow was performed and blood lactate was measured at the end of baseline and CPR. Sublingual microcirculation was assessed by the Sidestream Dark Field (SDF) technology during baseline, CA and CPR. Following microcirculatory parameters were assessed off-line separately for capillaries (≤20 µm) and other vessels: total and perfused vessel density (TVD, PVD), proportion of perfused vessels (PPV), microvascular flow index (MFI) and heterogeneity index (HI). RESULTS: In comparison to baseline the CA small vessel microcirculation was only partially preserved: TVD 15.64 (13.59-18.48) significantly decreased to 12.51 (10.57-13.98) mm/mm(2), PVD 15.57 (13.56-17.80) to 5.53 (4.17-6.60) mm/mm(2), PPV 99.64 (98.05-100.00) to 38.97 (27.60-46.29) %, MFI 3.00 (3.00-3.08) to 1.29 (1.08-1.58) and HI increased from 0.08 (0.00-0.23) to 1.5 (0.71-2.00), p = 0.0003 for TVD and <0.0001 for others, respectively. Microcirculation during ongoing CPR in small vessels reached 59-85 % of the baseline values: TVD 13.33 (12.11-15.11) mm/mm(2), PVD 9.34 (7.34-11.52) mm/mm(2), PPV 72.34 (54.31-87.87) %, MFI 2.04 (1.58-2.42), HI 0.65 (0.41-1.07). The correlation between microcirculation and global hemodynamic parameters as well as to lactate was only weak to moderate (i.e. Spearman's ρ 0.02-0.51) and after adjustment for multiple correlations it was non-significant. CONCLUSIONS: Sublingual microcirculatory parameters did not correlate with global hemodynamic parameters during simulated porcine model of CA and CPR. SDF imaging provides additional information about tissue perfusion in the course of CPR.
Keywords: Heart Arrest; laktáty; Cardiopulmonary resuscitation; srdeční zástava; Sublingual area; Cardiopulmonary Resuscitation; Hemoglobins; Animal model; Sus scrofa; Microcirculation; kardiopulmonální resuscitace; ženské pohlaví; Microscopy camera technology; zvířata; Sidestream dark field imaging; Lactates; Hemodynamics; Temperature; hemodynamika; Cardiac arrest; hemoglobiny; Female; mikrocirkulace; teplota; Animals